Professional Cycling and the Fight against Doping - Volker Robeck (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Doping seems to be well-organized and inherent in the system of professional cycling. This paper provides a theoretical approach, by using a multi-task (training and doping) principal-agent (team manager and cyclist) model, to illustrate the information asymmetry and conflicting objectives between both actors. Three settings are used to represent different situations in which the fight against doping takes place with varying intensity. The comparison of the equilibria in each setting reveals the influence of the fight against doping on the team members' behaviour. The analysis shows that team managers are interested in doping, and that current anti-doping institutions cannot suppress the abuse of forbidden drugs.
Keywords: 330